Advanced omniphobic membrane: fabrication via NIPS method using PVDF-HFP, TEOS, and PFDTMS - Abid, Monis (Springer Nature, 2024)
Amid the global water crisis, developing innovative solutions for sustainable water purification is crucial. Membrane distillation (MD) has emerged as a pivotal method with significant potential to address these challenges effectively. In this research endeavor, our team focused on creating and optimizing an omniphobic membrane utilizing a combination of Poly(vinylidenefluoride-co-hexafluoropropylene) (PVDF-HFP), Tetraethyl orthosilicate (TEOS), and Perfluorodecyltrimethoxysilane (PFDTMS) through the nonsolvent-induced phase separation (NIPS) methodology. The resultant membrane displayed a notable contact angle of 130°, underscoring its remarkable omniphobic properties. Various characterization techniques were used to evaluate the membrane's performance, including liquid entry pressure (LEP), porosity analysis, thickness determination, pore size quantification, and scanning electron microscopy (SEM). SEM images revealed enhanced surface roughness, which is critical for efficiency. Additionally, X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and energy-dispersive X-ray spectroscopy (EDS) provided insights into the membrane's crystalline structure and chemical composition.